A MULTIMODAL DISCOURSE ANALYSIS OF MEMES AS PROPAGANDA IN GLOBAL CONFLICT - Nabaa Khalid; Nur Syuhada Mohd Radzi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
Now, it is quite natural for propaganda to accompany the war but its form has evolved and expanded from the use of traditional media only to include the online media, through which memes play a big role for the public opinion moulding. Our paper is in-depth research on how one country made use of memes for their propaganda work during a period of political tensions (the 2026 one country – a superior country conflict, to be precise). To make our points vivid, we examined how memes with both texts and pictures as well as signs were used to send certain ideologies, and how the three elements of the memes worked co-operatively toward achieving that aim. The sample that we drew was 15 selected memes. We chose them per certain principles, that is, our purpose sampling. All those selected memes had been posted to the public by an official Twitter/X account of the One Country Embassy in South Africa, in particular. Combining Multimodal Discourse Analysis of Kress and van Leeuwen and the model of ideological representation by Van Dijk, this study tries to find out what is the role of the combination of language and images in a communicative context where persuasion is the main objective. The results reveal that besides functioning for entertainment purposes, memes can be viewed as a way or means through which the state makes its politics and culture known by, in a way, legitimizing its narratives or even portraying conflicts in a way favourable to itself. We want to underline that our paper is a significant contribution to the academic discourse on digital propaganda since it highlights how a multifaceted combination of language and images serves state purposes and, at the same time, is able to simplify the complex political events into catchy and persuasive bits of propaganda.